PEMANFAATAN EKSTRAK DAUN BABANDOTAN (Ageratum conyzoides) SEBAGAI BIOHERBISIDA GULMA RUMPUT TEKI (Cyperus Rotundus) - Hikmah, Arfa Ul; Bilkis, F.G; Maelani, D.G.; Triastinurmiatiningsih, - (Fakultas Matematika dan ilmu pengetahuan Alam. Universitas Pakuan.)
Weeds are detrimental due to lower agricultural yields due to competition in water acquisition, nutrients, living areas, degradation of yield quality, into host pests and diseases, poisoning plants due to toxic compounds or alleles. One of the weeds on agricultural produce is grass (Cyperus rotundus) because it has allelopathic compounds. At this time alternative weed control that is environmentally minded rampant done by looking for potency of phenol group compound from other plant so that can be utilized as bioherbisida. Babandotan (Ageratum conyzoides) containing active compounds such as saponins, flavonoids, tannins, essential oils and polyphenols are safe and environmentally friendly bioherbicides. The purpose of this study to determine the concentration of babandotan leaf extract that can inhibit the growth of weeds teki grass. Babandotan extract is made through the maceration method. Babandotan concentrations consist of 50%, 20%, 10% and 5% and control. Phytochemical test was conducted to determine the chemical content contained in babandotan leaf. The results showed that leaf extract of babadotan can inhibit the growth of grass teki at concentration 50%.Key words: Cyperus rotundus, Ageratum conyzoides, bioherbisida